Astronomical optics - Schroeder, Daniel J. (Academic Press, 2000)
The book provides a unified treatment of the characteristics of telescopes of all types, including telescopes whose performance is set by geometrical aberrations and the effect of the atmosphere, and those diffraction-limited telescopes designed for observations from above the atmosphere. It also contains thorough discussions of the principles underlying all spectroscopic instrumentation, giving special emphasis to grating instruments used with telescopes.